Hybrid numerical modelling of reverberation chambers - Zhao, Huapeng (2013)
This paper describes recent advancements in hybrid numerical modelling of reverberation chambers (RCs). Motivation of modelling an RC is first described, and challenges in RC modelling are pointed out. Shortcomings and advantages of conventional numerical methods are discussed, and hybrid techniques are introduced to overcome disadvantages of different numerical methods while retaining their respective strengths. Benefits of hybrid methods are then illustrated using numerical examples, and future works are finally suggested.